PERAN GURU PPKN DALAM MENINGKATKAN MINAT BELAJAR SISWA KELAS XII SMK PGRI 3 KOTA SERANG - Karo, Cuklesi Br; Sa'adiyyah, Ade Millatus; Marlina, Lina (UNTIRTA CIVIC EDUCATION JOURNAL, 2022)
The purpose in this study is to find out the role of pancasila education teachers and citizenship in increasing students' learning interest in the online learning process in class XII SMK PGRI 3 Kota Serang, to find out the factors inhibiting pancasila education teachers and citizenship in increasing students' learning interest in the online learning process in class XII SMK PGRI 3 Kota Serang and to know the efforts of the role of pancasila education teachers and citizenship in increasing interest in the bell. teach students in the online learning process in class XII SMK PGRI 3 Kota Serang. Research methods are used with descriptive qualitative techniques. The study took 15 (fifteen) respondents, consisting of 3 (three) teachers of Pancasila education and citizenship and 12 (twelve) students of class XII. With the result that the role of pancasila education teachers and citizenship in increasing students' learning interest is as a director of learning, teaching planner, teaching manager, assessment of learning outcomes, motivators and guides for students. Efforts that can be done by teachers are by cultivating feelings of pleasure in students, making student interest, attracting students' attention, inviting student involvement in following the online learning process.